Factors associated with the prevalence of Congenital Syphilis (Research, Society and Development, 2024)
Congenital Syphilis (CS) is a public health problem in several developing countries, such as Brazil, despite being preventable and a pathology that is easy to treat and control during pregnancy. The infectious disease can cause several negative outcomes, such as spontaneous abortion, premature birth, as well as serious neonatal sequelae such as deafness, blindness and mental disability. The objective of this study is to review articles that address the factors associated with the prevalence of Congenital Syphilis. This is an integrative review of the literature, with cross-sectional articles published from January 2019 to March 2024, in the electronic databases SciELO, MedLine and LILACS. The search strategy includes the following descriptors in Portuguese: (“congenital syphilis” AND “Brazil”); in addition to their respective counterparts in the English language. Studies indicate that failures in prenatal care, inadequate treatment, lack of partner treatment, early initiation of sexual activity and low education are factors associated with the prevalence of CS. Therefore, greater attention to pregnant women in situations of social vulnerability becomes essential, within the scope of primary health care. In addition to health education actions, emphasizing the importance of timely prenatal care, carrying out recommended therapy and treating the partner.